Nutritional and Rehabilitation goals in Acquired Brain Injury patients: a new decannulation protocol. (13th November 2019) - d'Angelo, M; Michelutti, A; Biasutti, E; Quattrin, R; Brusaferro, S
Abstract: Background: One of the first goals for the rehabilitation of patients with Acquired Brain Injury (ABI) is the removal of the tracheocannula: the aim is not only to allow respiration by airways and reduce respiratory complications but also to obtain rehabilitation of dysphagia and verbal communication: for this purpose from July 2017 the ABI unit of the Institute of Physical and Rehabilitation Medicine 'Gervasutta" adopted a new decannulation protocol, recommended by the Italian Society of Physical Medicine and Rehabilitation (SIMFER). Methods: Clinical data of ABI patients with tracheal cannula from May 2014 were collected as both process and outcome indicators associated with the adoption of the new protocol were defined. ABI patients were therefore divided into two groups depending on whether they were treated with or without the new procedure. Data have been processed with "Simple Interactive Statistical Analysis" (SISA) software. Results: A sample of 141 patients with tracheocannula was analyzed; among these 57 (40.4%) were treated with the new decannulation protocol. No statistical significant differences were found between the two groups in terms of systemic or respiratory complications, Functional Independence Measure (FIM) or Level of Cognitive Functioning (LCF) at the entrance as well as for both the time (days) between entry or tracheotomy and decannulation. However decannulation rate is significantly higher when the new protocol is applied (OR = 1.8; 95% CI = 1.2- 9.8; p = 0.01) as the time (days) between entry and oral feeding resumption (p < 0.001; 95% CI = -10 - -34 days). Conclusions: The introduction of the new protocol has allowed the achievement of both nutritional and rehabilitation goals with a significantly faster oral feeding resumption and an increase of decannulation rate and. Further efforts are needed to support its use in the future, with the aim of further improving of either process or outcome performances. Key messages: Promising prospects for the decannulation of patients with acquired brain injury. Achievement of nutritional and rehabilitation goals.